العفو عن الجرائم الدولية وتأثيره على فعالية مسار مقاربة العدالة الإنتقالية - لعناني، حسام (جامعة العربي بن مهيدي - أم البواقي, 2017)
بعد خروج الدولة ضحية النزاع المسلح من حالة الفوضى التي شهدت خلالها ارتكاب أبشع الجرائم من جرائم حرب وجرائم ضد الإنسانية وإبادة جماعية وانتهاكات جسيمة للقانون الدولي لحقوق الإنسان، تجد نفسها مجبرة على الأخذ بآليات عدة يشكل مجموعها ما يسمى بالعدالة الانتقالية، ولعل أكثر المسائل التي أثارت جدالا واسعا مسألة تأثير آلية العفو عن مرتكبي الجرائم الدولية في مسار العدالة الانتقالية. فقد يعتبر العفو من جهة أكثر الآليات خدمة للعدالة الانتقالية بما يوفره من جهد ووقت على الأنظمة القضائية الوطنية، كما قد يعتبر من جهة أخرى عائقا يقف في وجه العدالة الانتقالية إذا ما أستعمل بطريقة خاطئة تحفز سياسة الإفلات من العقاب وتولد شعورا بضياع حقوق الضحايا. تحاول هذه الدراسة الإجابة عن إشكالية مفادها: هل العفو آلية مدعمة ومحفز لنجاح مسار العدالة الانتقالية أم هي عائق يحول دون وصولها لأهدافها؟.
After the departure of the state victim of armed conflict from the chaos which has seen only commit the most heinous crimes of war crimes and crimes against humanity, genocide and gross violations of international human rights law, be obliged to take several mechanisms which constitutes the so-called transitional justice, and perhaps more transitional justice mechanisms that sparked a broad controversy is amnesty for the perpetrators of international crimes and their impact in the transitional justice process. Amnesty may be considered on the one hand in Service of Transitional Justice by offering of effort and time on the national judicial systems, as may be considered an obstacle standing in the face of transitional justice if Amnesty take the wrong way which stimulate the policy of impunity and generate a sense of the loss of the victims rights. This study answers the question: Is the amnesty mechanism supported the success of the transitional justice process or is it an obstacle prevents its arrival to its goals?
Keywords: العفو -- الجرائم الدولية -- العدالة الانتقالية -- الإفلات من العقاب -- القانون الدولى -- العفو عن الجرائم الدولية